Electrochemical valorization of waste activated sludge for short-chain fatty acids production - Jafari, Maasoomeh; Botte, Gerardine G. (Frontiers in Chemistry, 2022)
A tremendous amount of waste activated sludge (WAS) ends up in landfilling even after a substantial retention time during anaerobic digestion. This leftover activated sludge is an organic-rich material with the high potential to produce value-added chemicals such as short chain fatty acids (SCFAs). In the present study, a novel electrochemical conversion of activated sludge (E-WAS) was carried out on the surface of non-precious electrodes (nickel, stainless-steel and copper) in alkaline media at low applied potential and temperature. Cyclic voltammetry showed that Cu (II)/Cu (III) and Ni (II)/Ni(III) redox couple catalyzed the WAS oxidation reaction to produce SCFAs and hydrogen. The results revealed that Cu(II)/Cu(III) has higher catalytic oxidation capability towards SCFAs. Yields of 48.7, 21.4, and 14.6 mg SCFAs per g of volatile solids were achieved by using copper, nickel and stainless-steel as working electrodes, respectively. Post analysis characterization techniques indicate that copper oxide films lead to WAS oxidation. Total volatile solid removal of 30% was obtained at 35 ºC and 1.65 V in 0.2 M NaOH after 2 h of operation in an electrochemical digestor with copper electrodes which is more efficient than a conventional alkaline treatment (24 h, ⁓55%, 1M NaOH). Ammonia was produced as the by-product of E-WAS oxidation. The highest amount of ammonia (250 mg L-1) was obtained by using nickel as the working electrode after 2h operation at 35 °C and 1.35 V applied potential. The change in WAS morphology revealed that the copper oxide film is effective electrocatalyst for WAS disinfection.